CAUSES AND CONSEQUENCES OF THE CULTURAL REVOLUTION IN CHINA - pcadmin, pcadmin (Scholar Express Journals, 2025)
Storm clouds were gathering around the Great Helmsman. After the failure of the “Great Leap Forward”, the party elite was slowly but surely pushing the leader out of power. Mao watched passively as Liu Shaoqi and Deng Xiaoping turned his China 180 degrees. There were plenty of signs that Mao's time was running out. Bad news came from the neighboring Soviet Union. A coup had taken place, resulting in the overthrow of Nikita Khrushchev. The conspirators included almost the entire Politburo, including Leonid Ilyich Brezhnev. It seemed that the Soviet Union was merely ahead of China by a few years and that Mao was facing the same, if not a worse, fate. Mao finally became convinced that conspirators, capitalists, and revisionists could not be eradicated through mere party purges. The system of power in China had to be radically changed, the communist state had to be reinvented and reimagined.
Keywords: resulting; communist; Soviet Union; Helmsman